Iman melawan Nalar: Perdebatan Joseph Ratzinger dengan Juergen Habermas - R.B. Aditya Wahyu (Arete, 2022)
Pengarang       : Giancarlo Bosetti (ed.) Penerbit      : PT KanisiusTahun Terbit  : 2009Tebal             : 90 halamanISBN             : 978-979-21-2405-7